2017
DOI: 10.1111/cch.12476
|View full text |Cite
|
Sign up to set email alerts
|

The support needs of parents having a child with a chronic kidney disease: a focus group study

Abstract: Needs regarding balancing their personal life are seldom prioritized by parents as the child's needs are considered more important. Therefore, it is important that healthcare professionals should not only attend to the abilities of parents concerning their child's disease management, but also focus on the parents' abilities in balancing their responsibilities as a caregiver with their own personal life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
4
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 28 publications
(62 reference statements)
9
72
4
12
Order By: Relevance
“…Tong et al () found that parents felt that the illness constrained the parents’ social life; however, this improved after kidney transplantation. Similar to our study, it was found that friends and extended family provided significant practical support; however, lack of understanding of the family situation was commonly reported (Geense et al, ; Tong et al, ).…”
Section: Critical Interpretation and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tong et al () found that parents felt that the illness constrained the parents’ social life; however, this improved after kidney transplantation. Similar to our study, it was found that friends and extended family provided significant practical support; however, lack of understanding of the family situation was commonly reported (Geense et al, ; Tong et al, ).…”
Section: Critical Interpretation and Discussionsupporting
confidence: 88%
“…Parents constitute a core element of, and are responsible for, the family's well‐being, dynamics and social and emotional functioning. Parents need emotional support from peers, friends and healthcare professionals (HCP) to help them cope with their child's disease (Geense, Gall, Knoll, Cornelissen, & Achterberg, ; Tong, Lowe, Sainsbury, & Craig, ). They find it difficult to combine supporting their partner, talking about their feelings regarding the child's disease and coping with siblings’ feelings of being neglected (Geense et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For the development of this intervention, an extensive needs assessment was conducted, consisting of a literature study and five focus group interviews with parents [34]. This needs assessment revealed that online peer support was (the most) frequently mentioned need of parents, and it is often used by parental caregivers for emotional needs [5,6,31].…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with parents and healthcare professionals, intervention mapping was used: a protocol for the systematic development of theory-and evidence based health promotion interventions [10]. After conducting a needs assessment with parents (consisting of five focus group interviews) [11], defining program objectives, searching for theories and selecting practical applications, e-Powered Parents [Mijn Kinderniernet in Dutch] was developed [12]. E-Powered Parents consisted of three different components: 1) an informative part comprising information and videos about different kidney diseases, treatment possibilities, diets and (financial) regulations; 2) an interactive part consisting of a forum, chat room and an option to send private messages to share their experiences with other parents and healthcare professionals, and 3) an online training platform consisting of four different training modules (stress management, setting limits, communication and coping) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children with kidney disease in particular report difficulties balancing responsibilities as caregivers with personal self-care [56]. There is a need for intervention efforts aimed at preventing or reducing parenting stress among caregivers of children with chronic illness, but few specific interventions have been developed to accomplish this.…”
Section: Approach To Fetal and Neonatal Therapy For Epramentioning
confidence: 99%